Local politicians in the age of new media - Bjørnå, Hilde; Steinveg, Beate; Hernes, Hans-Kristian (Frontiers in Political Science, 2022)
This paper discusses the impact of new media on local politics and politicians in a highly digitalised and advanced democracy. Through case studies and interviews of elite representatives in three Norwegian municipalities, the paper's ambition is to gain further understanding of the use of new media at the local political level and how new media influence and shape the role of local political representatives. To this aim we engage with established literature on new media use in campaigns and as self-promotion, as well as literature on new media and democracy. The main findings are that the use of new media, particularly Facebook, is widespread, hardening the political debate, and especially straining for younger women. Moreover, new media contribute to the “professionalizing” of political communication as they require more strategic thinking around messaging and engagement. While they have in some ways contributed to bringing local representatives closer to the citizens and provided valuable information, they have also produced “echo-chamber” effects. In sum, new media provide challenges and opportunities that may impact one's willingness to stand as a representative and contribute to creating new “types” of local politicians.